Intratumoral injection of thermogelling and sustained-release carboplatin-loaded hydrogel simplifies the administration and remains the synergistic effect with radiotherapy for mice gliomas. (January 2018) - Liang, Hsiang-Kuang Tony; Lai, Xue-Shi; Wei, Ming-Feng; Lu, Szu-Huai; Wen, Wen-Fen; Kuo, Sung-Hsin; Chen, Chung-Ming; Tseng, Wen-Yih Isaac; Lin, Feng-Huei
Abstract: Background: Carboplatin, an antineoplastic agent, binds DNA and enhances radiotherapy (RT) effects. Carboplatin-loaded hydrogel (oxidized hyaluronic acid/adipic acid dihydrazide) enables the sustained drug release and facilitates the synergistic effect with RT. Purpose: We investigated the effectiveness and convenience of hydrogel carboplatin combined with RT for mice glioma. Materials and methods: Mouse glioma cells (ALTS1C1) were subcutaneously implanted in the right thigh of C57BL/6 mice on Day 0. The mice were categorized by treatments: sham, hydrogel, hydrogel carboplatin, aqueous carboplatin, RT, hydrogel carboplatin/RT, and aqueous carboplatin/RT. Hydrogel carboplatin (300 μg single dose on Day 7) or aqueous carboplatin (100 μg daily dose on Days 7, 8, and 9) was administered via intratumoral injection. RT was delivered a daily dose of 10 Gy on Days 8 and 9. Results: For mice administered hydrogel carboplatin/RT versus those administered aqueous carboplatin/RT, the 24-day tumor growth control rate and 104-day recurrence-free survival rate were 100% and 50% versus 100% and 66.7% ( p  = 0.648), respectively. However, mice receiving other treatments showed tumor progression by Day 24 and died within 40 days of tumor cell implantation. Conclusions: Hydrogel carboplatin simplified intratumoral drug delivery and remained the synergistic effects with RT, which is potential for clinical applications.